Effect of the renin-angiotensin system on the exacerbation of adrenal glucocorticoid steroidogenesis in diabetic mice: Role of angiotensin-II type 2 receptor - Chaves, Amanda da Silva; Magalhães, Nathalia Santos; Insuela, Daniella Bianchi Reis; Silva, Patrícia Machado Rodrigues E.; Martins, Marco Aurélio; Carvalho, Vinicius Frias (Frontiers in Endocrinology, 2022)
Prior investigation shows an increase in the activity of both hypothalamus-pituitary-adrenal (HPA) axis and the renin-angiotensin system (RAS) in diabetic patients. Moreover, activation of angiotensin-II type 1 receptor (AT1) has been associated with adrenal steroidogenesis. This study investigates the role of RAS on the overproduction of corticosterone in diabetic mice. Diabetes was induced by intravenous injection of alloxan into fasted Swiss-webster mice. Captopril (angiotensin-converting enzyme inhibitor), Olmesartan (AT1 receptor antagonist), CGP42112A (AT2 receptor agonist) or PD123319 (AT2 receptor antagonist) were administered daily for 14 consecutive days, starting 7 days post-alloxan. Plasma corticosterone was evaluated by ELISA, while adrenal gland expressions of AT1 receptor, AT2 receptor, adrenocorticotropic hormone receptor MC2R, pro-steroidogenic enzymes steroidogenic acute regulatory protein (StAR), and 11β-hydroxysteroid dehydrogenase type 1 (11βHSD1) were assessed using immunohistochemistry or western blot. Diabetic mice showed adrenal gland overexpression of AT1 receptor, MC2R, StAR, and 11βHSD1 without altering AT2 receptor levels, all of which were sensitive to Captopril or Olmesartan treatment. In addition, PD123319 blocked the ability of Olmesartan to reduce plasma corticosterone levels in diabetic mice. Furthermore, CGP42112A significantly decreased circulating corticosterone levels in diabetic mice, without altering the overexpression of MC2R and StAR in the adrenal glands. Our findings revealed that inhibition of both angiotensin synthesis and AT1 receptor activity reduced the high production of corticosterone in diabetic mice via the reduction of MC2R signaling expression in the adrenal gland. Furthermore, the protective effect of Olmesartan on the overproduction of corticosterone by adrenals in diabetic mice depends on both AT1 receptor blockade and AT2 receptor activation.